Risk management implementation in the Klang Valley construction industry from contractors perspective / Noor Fara Waheeda Ismail - Ismail, Noor Fara Waheeda (Faculty of Architecture, Planning and Surveying, 2013)
Construction is one of the highest risk business exist. Generally the overrun of the cost and time in project are mainly caused by risks. However, it was found that although the risk management process in Malaysian construction industry has been introduced, most of them are not well structured and not implemented in a formal maimer. Many contractors still have a poor level of awareness in the application of risk management. Therefore, there are still high risks arise in Malaysian construction industry. As a result, this has led contractors struggling to complete the contract on schedule, within the clients budget and quality parameters. The risks naturally exist in every construction projects and they are hardly to eliminate. Contractor often has negative view on risk management. A wider understanding on the relevance and characteristics in risk management is needed. This mean its essential for contractor parties to understand well in risk management. Thus the objective of this study was to recommend factors to improve the implementation of risk management in construction projects and also include risk management as part of a construction project where contractors usually have a higher chance to face the project risk and their impacts more frequently. Therefore, in order to conduct this study, Quantitative method has been selected. Quantitative method involves in administrating questionnaire and interviews to the sample group to collect required data.